PENGARUH WARNA DAN GAMBAR TERHADAP TINGKAT RECOGNIZING DAN MATCHING SIMBOL VISUAL DI AREA PUBLIK - Lenka R. Peruba; Vivi Triyanti (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
Symbol is diagram or shape that represents an idea. Symbol should match to values with the intention to viewers can recognize it with no mistaken in interpretation. Therefore, recognizing and matching in interpreting symbol should be considered Conducting experimental designs, this researchconcerns on 2 factors that predicted have certain relationship to recognizing and matching value of the symbol in public area, which are color and shape. The results showed the difference of colors and shape had significant effect in matching value. Mean while, only shape that had effect in recognizing value.Symbol wirh color green had the highest matching value (1), where as symbol with white in black color has least matching value (0.525) Moreover, regression linear analysis using dummy variable indicates that person with lower age tend to have less recognizing capability than the younger one and malegenerally had higher recognizing and matching value than female.